Alteration of the Oligodendrocyte Lineage Varies According to the Systemic Inflammatory Stimulus in Animal Models That Mimic the Encephalopathy of Prematurity - Favrais, Geraldine; Bokobza, Cindy; Saliba, Elie; Chalon, Sylvie; Gressens, Pierre (Frontiers in Physiology, 2022)
Preterm birth before the gestational age of 32 weeks is associated with the occurrence of specific white matter damage (WMD) that can compromise the neurological outcome. These white matter abnormalities are embedded in more global brain damage defining the encephalopathy of prematurity (EoP). A global reduction in white matter volume that corresponds to chronic diffuse WMD is the most frequent form in contemporary cohorts of very preterm infants. This WMD partly results from alterations of the oligodendrocyte (OL) lineage during the vulnerability window preceding the beginning of brain myelination. The occurrence of prenatal, perinatal and postnatal events in addition to preterm birth is related to the intensity of WMD. Systemic inflammation is widely recognised as a risk factor of WMD in humans and in animal models. This review reports the OL lineage alterations associated with the WMD observed in infants suffering from EoP and emphasizes the role of systemic inflammation in inducing these alterations. This issue is addressed through data on human tissue and imaging, and through neonatal animal models that use systemic inflammation to induce WMD. Interestingly, the OL lineage damage varies according to the inflammatory stimulus, i.e., the liposaccharide portion of the E.Coli membrane (LPS) or the proinflammatory cytokine Interleukin-1b (IL-1b). This discrepancy reveals multiple cellular pathways inducible by inflammation that result in EoP. Variable long-term consequences on the white matter morphology and functioning may be speculated upon according to the intensity of the inflammatory challenge. This hypothesis emerges from this review and requires further exploration.